Kinerja Perawat Instrumen dalam Melaksanakan Manajemen Alat Operasi Herniotomi Hernioraphy (HTHR) di Instalansi Bedah Sentral RSUD Kanjuruhan Kepanjen - Wahyuningsri Wahyuningsri; GM Sindarti; Irawan Irawan (STIKes Patria Husada Blitar, 2017)
Nurse instrument is professional nursing personnel who is given authority and responsibility in the management of surgical instruments of any type of surgery, has the task of covering before, during, and after surgery action. The absence of SOP (Standart OperationalProcedure)Â makes every action only based on the experience and habits of each surgical operator. The purpose of this study is to determine the performance of nurses in implementing instrument management tools in a kind of herniotomic herniospheric instrument operation management at central surgical installation of Kanjuruhan Kepanjen Hospital. The research design used is descriptive observative. A population of 30 nurses at a central surgical installation. The number of samples used in this study is 10 nurses of instrument according to the inclusion criteria in charge. In operating room for herniotomic hernioraphy (HTHR) surgery. Sampling technique used is Total Sampling. Taking data by observation with check list. The result of research on the performance of nurse instrument in implementing the management of Herniotomic Herniospheric operation tool before and during the 100% surgical action not yet comply with the SOP (Standart OperationalProcedure), the performance of the instrument nurse after surgery is 100% appropriated. Further research recommendations are expected to continue research on the performance of nurse instruments on others types of operations for all nurses assigned to operating rooms.